THE STUDY OF OUTDOOR LEARNING ON ONLINE TEACHING MEDIA FOR YEAR 4 MECHANICAL ENGINEERING STUDENT, FACULTY OF TECHNICAL EDUCATION, RAJAMANGALA UNIVERSITY OF TECHNOLOGY KRUNGTHEP - Chiranorawanit, Sukit; Suthisripok, Saranee (RMUTK Journal of Liberal Arts, 2020)
The study of Outdoor Learning on Online Teaching Media for the 4th Year Mechanical Engineering student, Faculty of Technical Education, Rajamangala University of Technology Krungthep is to find the students’ learning achievement from outdoor learning on online teaching media. The purposive sample technique were used to select 12 of the 4th year mechanical engineering students, Faculty of Technical Education, Rajamangala University of Technology Krungthep. The research instruments were the pre and posttests in the form of Fill in the bank type. The experts assessed the content of the test. Respondents did the pretest before attending the Outdoor Learning on Online Teaching Media. And after the outdoor media activity, respondents did the posttest. Frequency and percentage were utilized to calculate the raw data. The results of this study revealed that the regarding pre-test: 17 per cent (S.D 2.31) could explain the meaning of online teaching media, 10 per cent (S.D 2.92) could demonstrate the steps and planning of how to do the online teaching media whereas the post-test: 58 percent (S.D 3.06) could explain the meaning of the online teaching media, 100 percent (S.D 4.32) could demonstrate the steps of how to do the online teaching media, and 83 per cent (S.D 4.26) could demonstrate the planning of how to do the online teaching media. Pretest scores and Posttest score were discovered significantly different at .01 level. Hence, this study project of outdoor learning on online teaching media could assist to increase higher students’ achievement.